2007
DOI: 10.1007/s10571-007-9153-1
|View full text |Cite
|
Sign up to set email alerts
|

Editing of AMPA and Serotonin 2C Receptors in Individual Central Neurons, Controlling Wakefulness

Abstract: (1) Pre-mRNA editing of serotonin 2C (5-HT2c) and glutamate (Glu) receptors (R) influences higher brain functions and pathological states such as epilepsy, amyotrophic lateral sclerosis, and depression. Adenosine deaminases acting on RNA (ADAR1-3) convert adenosine to inosine on synthetic RNAs, analogous to 5-HT2cR and GluR. The order of editing as well as mechanisms controlling editing in native neurons is unknown. (2) With single-cell RT-PCR we investigated the co-expression of ADAR genes with GluR and 5-HT2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
1
16
0
1
Order By: Relevance
“…The level of expression of ADAR2 does not correlate directly with the enzyme activity alone, but also depends on isoform distribution. 13,14,60 We found that fluoxetine upregulated all 4 isoforms, although it upregulated Ld to a larger extent than the Sd isoform and Sc to a larger extent than the Lc isoform. High levels of expression of both the Sd and Sc isoforms indicate an increase of editing activity, at least of the GluK2 Q/R site in hypothalamic tuberomamillary neurons.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…The level of expression of ADAR2 does not correlate directly with the enzyme activity alone, but also depends on isoform distribution. 13,14,60 We found that fluoxetine upregulated all 4 isoforms, although it upregulated Ld to a larger extent than the Sd isoform and Sc to a larger extent than the Lc isoform. High levels of expression of both the Sd and Sc isoforms indicate an increase of editing activity, at least of the GluK2 Q/R site in hypothalamic tuberomamillary neurons.…”
Section: Discussionmentioning
confidence: 77%
“…High levels of expression of both the Sd and Sc isoforms indicate an increase of editing activity, at least of the GluK2 Q/R site in hypothalamic tuberomamillary neurons. 14 Thus, fluoxetine not only upregulates the expression of ADAR2 but also enhances its editing activity. The signalling events linking 5-HT 2B activation with upregulation of ADAR2 are unknown, but we have previously shown that upregulation of cPLA 2 was dependent on metalloproteinase-mediated release of an epidermal growth factor (EGF) receptor agonist and subsequent stimulation of the EGF receptor by this agonist, leading to ERK 1/2 activation and entry of p-ERK 1/2 into the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, mice chronically treated with fluoxetine also exhibited decreased 5-HT 2c R E site-editing in the brain (Gurevich et al, 2002). Although the expression level of ADAR2 mRNA is one determinant of the efficiency of GluR2 Q/R site-editing, it has been reported that editing extents of the various A-to-I editing sites in 5-HT 2c R mRNA correlated with the mRNA expression level of none of the members of ADAR families in cells from the rat hypothalamic tuberomamillary nucleus (Sergeeva et al, 2007). Taking our data and these 15 reports together, antidepressants might have modulatory effects on A-to-I RNA editing sites in various mRNAs by direct upregulation of ADAR2 mRNA or other mechanisms.…”
Section: Discussionmentioning
confidence: 99%